Evaluasi dan Perbaikan Usability Situs Web Niagara Rafting dengan menggunakan Metode Heuristic Evaluation - Fadillah Dwi Wicaksana; Buce Trias Hanggara; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Niagara Rafting is a website developed by Niagara Adventure to display a profile of Niagara Rafting and find out what products and services are offered. Based on the results of interviews with users, it is known that there are problems related to usability aspects, namely learnability and satisfaction. Since the first time the website released, the evaluation carried out by Niagara Rafting was limited to the functionality and did not pay attention to the usability aspect of the user interface to overcome the usability problems that were found. Heuristic evaluation is a method for conducting usability testing properly because it involves an expert who has a deep understanding of usability as an evaluator in this study. Each usability problem found will be given a severity rating from 0 to 4. There are 2 stages of heuristic evaluation, namely early stage heuristic evaluation and late stage heuristic evaluation. The initial heuristic evaluation carried out an assessment of the original object, namely the Niagara Rafting website and found 18 usability problems. Recommendations for improvement are made in the form of a high-fidelity prototype by taking into account the recommendations provided by the evaluators and guidelines. The final heuristic evaluation carried out an assessment of the improvement design resulting in 3 usability problems and there were old usability problems, but the severity rating value was reduced from 4 to 2 and from 2 to 1.